PENGEMBANGAN NILAI AGAMA MELALUI METODE BERMAIN PERAN PADA ANAK USIA DINI - Jaberia; Fadhilla Dwi Yanti Mulyono; Eka Damayanti; Aeni Tasnim; Erwin Syarif (NANAEKE: Indonesian Journal on Early Childhood Education, 2022)
The development of religious values in early childhood is very important. One way that can be done in developing religious values in learning is by using role-playing methods. This study aims to find out the importance of role-playing in the development of religious values in early childhood. This type of research is a library study research (Library Research) with data collection using documentation techniques from journals published in 2015-2022 and reference books that are in accordance with the focus of the research. The data analysis used in this study is content analysis. The results of the study show that role-playing methods, especially in the role-playing activities of doctors, becoming priests, and being a helper child (almsgiving) can develop and increase children's religious values.